Ammonia assimilation: A double-edged sword influencing denitrification of Rhodobacter azotoformans and for nitrogen removal of aquaculture wastewater. (February 2022) - Li, Zhen; Li, Lu; Sun, Haoyu; Wang, Wenjuan; Yang, Yuying; Qi, Zhengliang; Liu, Xinli
Graphical abstract: Highlights: Low NH4 + -N concentrations accelerates denitrification while high concentrations are inhibitory. NH4 + -N concentration > 0.3 mM inhibits NO reduction causing denitrification depression. Denitrification efficiency is improved via optimizing initial NH4 + -N concentrations. Abstract: NO3 − -N and NH4 + -N are two prevalent nitrogenous pollutants in aquaculture wastewater posing a significant health risk to aquatic animals. R. azotoformans ATCC17025 can rapidly denitrify to remove NO3 − -N, assimilating NH4 + -N. The study investigated the influence of ammonia assimilation on bacterial denitrification. Results revealed that low concentration of NH4 + -N (≤0.3 mM) accelerated denitrification, whereas high concentration inhibited it. RT-qPCR indicated that the inhibition of NO reduction under high concentration of NH4 + -N was the primary cause of denitrification depression, whereas low concentration of NH4 + -N enhanced the synthesis of practically all enzymes involved in denitrification. Finally, nitrogen-rich aquaculture effluent was effectively treated in lab-scale using a semi-continuous operation that provided an appropriate NH4 + -N concentration for denitrification. This semi-continuous operation treated wastewater 2 times faster than the batch operation and the content of nitrogen decreased to effluent standard. The study can provide guidance for nitrogen removal of aquaculture wastewater with bioaugmentation.